'Cattle infectivity is driving the bTB epidemic'. (7th December 2019) - McGill, Iain; Jones, Mark
Abstract : Iain McGill and Mark Jones argue that recent data released by the APHA show that it is the prevalence or 'infectivity' of cattle that is sustaining bTB infection and driving transmission of Mycobacterium bovis to new herds.